Integrating literature and music for classroom teaching with an interactive story book - Jinky Jane C Simeon; Jacqueline Pugh-Kitingan (Penerbit UMS, 2021)
This paper focuses on the development of an interactive story book based on a Rungus children’s folk song (longoi tanganak). The book was developed to encourage children to express their ideas through storytelling, music and movement. This study aims to explore how an interactive book can be used in the music classroom and outlines ways in which music and movement can be integrated while reading a story. Field trips were conducted in Kudat and Pitas, Sabah to collect longoi tanganak from elderly Rungus singers recommended by village heads. Following that, a Sabah-based story was written and a song containing musical characteristics suitable for children’s singing activities were incorporated into the story. Finally, a survey was sent to 12 selected music teachers to answer the following questions: (1) What age group could use this storybook? (2) What genres of children’s literature do you use in your lessons? (3) How would you use this storybook in your music classroom? and (4) Why do you use children’s literature in your music lessons? In addition to that, two music teachers were selected from the pool of respondents and were video recorded teaching a music lesson that incorporated this story book. The results of this study revealed that children were highly engaged in the lesson, responding and actively participating in the reading of the story. This included vocal, movement and instrument exploration. Young children also learned extra skills in sign language and memorising words through the composed song, adapted from a Rungus longoi tanganak (children’s song). This product is an innovation that is suitable to be used as a teaching aid among preschool, kindergarten, and primary school children.